Experiences with cytoreduction surgery plus hyperthermic intraperitoneal chemotherapy in Taiwan. Issue 26 (June 2017) - Hsieh, Mao-Chih; Lu, Chang-Yun; Chang, Wei-Wen; Wu, Szu-Yuan; Hsiao, Ping-Kun; Liu, Tse-Jia
Abstract : Abstract: Our hospital was the first institution to offer cytoreduction surgery (CRS) plus hyperthermic intraperitoneal chemotherapy (HIPEC) in Taiwan. Therefore, we report our experience and outcomes among patients who underwent HIPEC. Since 2002, 164 eligible patients underwent HIPEC, and we excluded cases of laparoscopic or prophylactic HIPEC. The cases were categorized according to whether they were treated before 2012 (Period 1: 80 cases) or after 2012 (Period 2: 84 cases). The rates of surgical morbidity were 46.3% during Period 1 and 20.2% during Period 2 ( P  < .01), and the rates of severe complications were 25% during Period 1 and 9.5% during Period 2 ( P  < .01). The 5-year overall survival rate was 35.8%, with rates of 13.4% for gastric cancer, 27.3% for colon cancer, 70.0% for appendiceal cancer, and 52.4% for ovarian cancer (median follow-up: 34 months). The survival rate was 42.1% when we achieved a cytoreduction score of 0/1, compared with 21.1% in the group with a cytoreduction score of 2/3 ( P  < .01). Severe complications were associated with a 5-year survival rate of 23.4%, compared with 37.9% among cases without severe complications ( P  = .01). Complete cytoreduction was achieved in 78.6% of the patients if they underwent their first surgery at our hospital. We have become an experienced hospital for CRS plus HIPEC. Although our complication rate for CRS plus HIPEC was high, it was within the acceptable range. Long-term survival was achieved in a few cases.